Pengetahuan, Sikap dan Keterampilan Guru Sebagai Prevensi terhadap Kekerasan Seksual Pada Anak - Mentari Marwa (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
This paper aims to examine the provision of child protection training at the elementary school teachers as primary prevention of child sexual abuse to increase knowledge, attitudes and skills to convey information in Tulungagung, East Java. The research method using untreated control group design with pre-test and post-test. There are 21 elementary school teachers who are involved in the research. The instrument used was a questionnaire, observation. Test Mann Whitney U-test to test for differences in gain score the experimental group and the control group. The results showed no significant effect giving child protection programs against KSA by Guru to the increase of knowledge, attitudes, and skills of teachers as primary prevention of sexual assault at elementary school children in Tulungagung, East Java, as indicated by the results of Mann Whitney p value below a significant level 0,05 (p <0.05)